Tapered plastic optical fiber sensor for dengue non-structural protein 1 (Ns1) detection - Yusof, N.F.; Ibrahim, Fatimah; Rahman, H.A.; Adwan, S.; Harun, Sulaiman Wadi (National Institute of Optoelectronics, 2015)
A simple fiber optic sensor is proposed and demonstrated for detection of different concentration of dengue non-structural protein 1 (NS1) using a tapered plastic optical fiber (POF). The working mechanism of the device is based on intensity modulation technique where the transmitted light intensity variation is measured when the probe is immersed into dengue NS1 antigen and antibody solution with various concentrations. The dengue NS1 antigen and antibody of various concentrations (1x10-2, 1x10-3, 1x10-4, 1x10-5, 1x10-6, 1x10-7, 1x10-8 mg/mL) were prepared by serial dilution of a stock concentration of 1mg/ml with phosphate buffer saline solution. The tapered POF is fabricated through a chemical etching method by using acetone and deionized water to achieve a waist diameter and length of 0.45 mm and 25 mm, respectively. For detection of dengue NS1 antigen, as the solution concentration varies from 1x10-8 mg/mL to 1x10-2 mg/mL, the output voltage of the sensor reduces linearly from 1.21 mV to 1.17 mV with a slope sensitivity of 0.004 mV/ (mg/mL) and a linearity of 92.61%. As for detection of dengue NS1 antibody, the tapered POF based sensor produces a sensitivity of 0.84 mV/ (mg/mL) with a linearity of 98.61%.